Cutaneous amyloid is a biomarker in early ATTRv neuropathy and progresses across disease stages. Issue 9 (9th August 2022) - Freeman, Roy; Gonzalez‐Duarte, Alejandra; Barroso, Fabio; Campagnolo, Marta; Rajan, Sharika; Garcia, Jennifer; Kim, Jee Young; Wang, Ningshan; Orellana, Lucas; Gibbons, Christopher
Abstract: Objective: To determine the sensitivity and specificity of cutaneous amyloid deposition in relation to patient‐reported measures in the earliest disease stage of hereditary ATTR amyloidosis (ATTRv). Methods: In a cross‐sectional study, we analyzed 88 individuals with TTR mutations, 47 of whom were in the earliest disease stage and without clinically evident neuropathy, 12 healthy controls, and 13 disease controls with diabetes. All participants' neuropathy symptoms and signs were assessed using validated patient and clinician‐reported measures and 3‐mm skin punch biopsies were immunostained using protein gene product 9.5 and Congo Red. Results: Amyloid can be detected in the earliest disease stages in up to 86% of patients with ATTRv amyloidosis. Amyloid was not detected in healthy individuals or individuals with diabetic peripheral neuropathy supporting a sensitivity of 86% and a specificity of 100%. The cutaneous deposition of amyloid correlates with neuropathy sensory symptoms, measured with the Neuropathy Total Symptom Score‐6 ( R  = 0.46, p  < 0.01); pain measured with the Brief Pain Symptom Inventory ( R  = 0.44, p  < 0.05); autonomic symptoms, measured with the Boston Autonomic Symptom Questionnaire ( R  = 0.38, p  < 0.05); and quality of life measured with the Norfolk Diabetic Neuropathy Quality of Life Questionnaire ( R  = 0.44, p  < 0.05). Individuals with amyloid deposition were more likely to have sensory symptoms, pain, autonomic impairment, and reduced quality of life than ATTRv patients without amyloid deposition. Interpretation: These findings have implications for understanding the earliest manifestations of the clinical phenotype of ATTRv‐associated neuropathy, for the pathophysiological construct of disease staging, and for timing the introduction of disease‐modifying therapy.